Estimation of Hypertension Prevalence Among Diabetic Patients with Respect to Certain Covariates - Ogunmola, Adeniyi Oyewole; Uhembe, Solomon (Darul Yasin Al Sys, 2025)
This study investigates the risk factors associated with the prevalence of hypertension among diabetic patients in Jalingo, Taraba State, Nigeria, using logistic regression analysis. The results indicate a significantly high prevalence rate of hypertension among diabetic individuals, estimated at approximately 89.8%, with a 95% confidence interval ranging from 86.3% to 93.3%. The odds of a diabetic patient developing hypertension are about 8.8 times higher than not developing it. Logistic regression analysis identified systolic blood pressure and a family history of diabetes as significant predictors of hypertension. Specifically, a one-unit increase in systolic blood pressure corresponds to a 9.14% increase in the odds of being hypertensive, with the 95% confidence interval for the true odds ratio ranging from 5.59% to 12.82%. Additionally, diabetic patients with a family history of diabetes exhibit a 296.81% higher likelihood of developing hypertension compared to those without such a history, with the confidence interval for this odds ratio spanning from 7.65% to 1362.73%. These findings highlight the importance of monitoring systolic blood pressure and family history as key covariates in predicting hypertension risk among diabetic populations. Overall, the binary logistic regression model demonstrates robust predictive power for identifying hypertensive risk among diabetic patients based on these factors.